The International Competitive Position of the United States and the Balance of Payments Prospect for 1968 - Johnson, Harry G. (The Review of Economics and Statistics, 1964)
Harry G. Johnson, The International Competitive Position of the United States and the Balance of Payments Prospect for 1968, The Review of Economics and Statistics, Vol. 46, No. 1 (Feb., 1964), pp. 14-32